ANALISIS PENEMPATAN PEGAWAI DENGAN KESESUAIAN KEPRIBADIAN DAN PRESTASI KERJA PEGAWAI - Darmawan M Yakup (Gorontalo Management Research, 2020)
This study aims to analyze the placement with the suitability of personality and work performance of employees at Management Unit the Jalaludin Airport, Gorontalo. Data collection was carried out by distributing questionnaires to research respondents. The population and research sample are employees with a total sample of 87 people. The method of analysis used multiple linear regression which was processed using Statistical Product Service Solution (SPSS) applications. Data testing was preceded by validity and reliability tests. Research hypothesis testing was carried out partially and simultaneously. Research findings (1) personality has a positive and significant effect on placement. (2) work performance has a positive and significant effect on employment. (3) collectively, personality and work performance have a positive and significant effect on employee placement.